United States of America Policies in Managing Treats of Drugs from Mexico (2017-2019) - Hendra Maujana Saragih; Muhammad Zulham; Laras Deaziska (Universitas Komputer Indonesia, 2021)
Drugs has become a trend among the US – Mexico citizens that resulted imbalance in the national security of each country especially in the border area between US – Mexico. In this study, author use the national interest theory with the concept of national security and Transnational Organized Crime. By using descriptive qualitative research, this study aims to determine the efficiency of US policies that were continued by President Donald Trump. Even though the relationship between Mexico and the US is going-well and President Donald Trump is taking serious way for handling drug abuse in the US, unfortunately, the large sense of dependence from US citizen on drugs makes the policies that have been implemented inefficient. In addition, President Donald Trump’s policy can also have other impacts, such as an increase in the number of illegal immigrants entering the US through the border wall and an increasing number of the availability of several types of drugs such as heroin and marijuana in some states. Keyword : Drugs, Drug Trafficking, Drug Abuse, Mexico Cartel